Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Pegawai Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Sleman DIY - Hariyati, Ike; Ika Sunardi, Andhina (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2024)
The aim of this study is to examine the Influence of Leadership Style and Work Motivation on Employee Performance at the Department of Population and Civil Registration Office of Sleman Regency, DIY. The research method employed is quantitative with a descriptive approach. The data utilized consists of primary data obtained through the distribution of questionnaires to all employees of the Department of Population and Civil Registration Office of Sleman Regency, DIY. The sampling technique used in this research is saturation sampling, with a sample size equal to the entire population, totaling 83 individuals. Data analysis employed multiple linear regression analysis. The research findings indicate that the Leadership Style variable has a partial influence on Employee Performance as evidenced by the computation in Table 4.11, with a calculated t-value of 4.191 > the critical t-value of 1.990. Work Motivation also significantly affects Employee Performance with a calculated t-value of 4.853 > the critical t-value of 1.990, as shown in Table 4.12. Simultaneously, both Leadership Style and Work Motivation collectively influence Employee Performance at the Department of Population and Civil Registration Office of Sleman Regency, DIY, supported by an F-value of 28.759 greater than the critical F-value of 3.11